Probiotics and periodontal disease - Geraldo, Barbara Maria Corrêa [UNESP]; De Oliveira, Felipe Eduardo [UNESP]; De Oliveira, Luciane Dias [UNESP]; Anbinder, Ana Lia [UNESP] (My University, 2016)
During the last decade, new therapies involving the host response modulation in periodontal disease have been tested, and recent studies demonstrate that some probiotics are beneficial to oral health, decreasing the indicators of periodontal disease. Probiotics are defined by the World Health Organization as live microorganisms that can offer health benefits to the host. The most commonly studied genera that fulfill this definition are Lactobacillus, Bifidobacterium and Streptococcus. There are several mechanisms proposed to explain the probiotics’ actions on oral health, including the competition with pathogenic bacteria for adhesion sites on dental surfaces, modification of the oral environmental conditions via alteration of pH and/or oxidation-reduction potential, production of antimicrobial substances, stimulation of the nonspecific immunity and modulation of the humoral and cellular immune response. This chapterreviews the literature about the use of probiotics in periodontal disease, including in vitro, in vivo and clinical studies, in order to improve the understanding of probiotics’ role in periodontal disease and discusses the effectiveness of their use as a therapy for periodontitis.
Keywords: Lactobacilllus; Periodontal disease; Periodontitis; Probiotics